Évaluation de l'activité antimicrobienne des huiles essentielles de Artemesia herba alba de la région de El-Bayadh sur quelques germes pathogènes - KHEDROUGUI, Zahera; BOUHELLA, Hanane (My University, 2022)
The development of antibiotic resistance in micro-organisms has become a major problem. This is why our work has focused on the valorization of a plant species growing in spontaneous state in the semi-arid zones of Algeria, named Artemisia herba alba, by evaluating the antimicrobial activity of there essential oils. The essential oils of the dry leaves of Artemisia herba alba from Brezina region of El-bayadh (Algeria), were Extracted by steam distillation which allowed us to obtain a yield of .081%. A group of microorganisms provided by medical laboratories consisting of E. coli, Shigella dysenteriae, Pseudomonas aeroginosa, Staphylococcus aureus, Enterococcus faecalis and Candida albicans, was tested to verify the effectiveness of Artemisia herba alba essential oils. An antibiogram and an antifungigram were used to select 10 most resistant isolates, which are the subject of an aromatogram by the method of diffusion in a solid medium. This technique led us to quantitatively confirm the antimicrobial activity of the essential oils of Artemisia herba alba on the 10 isolates studied by determining the minimum inhibitory concentration (MIC). The results of the aromatogram and the MIC obtained from our experiments show that isolats of Staphylococcus aureus, Enterococcus faecalis are the most sensitive to essential oils of Artemisia herba alba with inhibition zones varying between 16 and 19 mm in diameter and values MIC between 0.312 and 0.625 μl/ml.
Keywords: Antimicrobial resistance; Essential oils; Artemisia herba alba; Antimicrobial activity; MIC